Penanaman nilai-nilai Ahlussunnah Wal Jama'ah An-Nahdliyyah pada Siswa MTs Manba’ul Ulum Kabul Lombok Tengah - Eny Fatimatuszuhro Pahlawati; Eko Hadi Wardoyo; Ahmad Akhirudin (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2022)
This study aims to determine the efforts to instill the values ​​of Ahlussunnah Wal Jama'ah An-Nahdliyyah at MTs Manba'ul Ulum Kabul, Central Lombok. This research is qualitative by conducting research at MTs Manba'ul Ulum Kabul, Central Lombok. The data collection method is through observation, interviews and intensive approaches with students, while the data analysis uses the Miles and Huberman method which suggests that qualitative analysis is carried out interactively and carried out continuously, namely through reduction, data display and conclusion. drawing or verification. The results of this study indicate that the inculcation of the values ​​of Ahlussunnah Wal Jama'ah An-Nahdliyyah is carried out through the lecture and discussion method, while the efforts made by inculcating the attitude of tawasut, tawazun and tasammuh as well as doing amar ma'ruf nahi munkar, so as to produce students who have good character, have high tolerance and always be humble in carrying out daily life.